Effect of compression garments on delayed-onset muscle soreness and blood inflammatory markers after eccentric exercise: a randomized controlled trial - Kim, Jieun (J Exerc Rehabil, 2017)
The purpose of this study was to investigate how compression garments, applied after eccentric exercise, can affect delayed onset muscle soreness (DOMS) and inflammatory markers. Sixteen healthy male university students enrolled in this study and were randomly assigned to either the compression garment group (CG, n=8) or control group (CON, n=8). All participants performed two sets of eccentric exercise using elbow flexor with 25 repetitions per set on a modified preacher curl machine. Maximal isometric strength was measured before exercise and immediately, 24, 48, 72, and 96 hr after eccentric exercise. Muscle soreness was measured before exercise and 24, 48, 72, and 96 hr after eccentric exercise. Creatine kinase (CK) activity and tumor necrosis factor-alpha (TNF-α) levels were also measured before exercise and 3, 6, 24, and 48 hr after exercise. A repeated measures analysis of variance was used for statistical analysis. The CG group reported faster recovery of maximal isometric strength following exercise (P<0.001) and lower muscle soreness during the recovery period than the control group (P<0.05). However, there were no significant differences in either CK activity or TNF-α levels between the two groups (P>0.05). In conclusion, wearing compression garments during the postexercise period can be an effective way to reduce DOMS and accelerate the recovery of muscle function.